The Kingdom of Rus' - Raffensperger, Christian (Book collections on Project MUSE., 2017)
The Kingdom of Rus' challenges the perception of Rus' as an eastern "other"--Advancing the idea of the Rus' as a kingdom deeply integrated with medieval Europe.